Expertise in second language learning and teaching (Palgrave MacMillan, 2005)
In this volume, methodologies for establishing what constitutes expert practice in language teaching and learning are discussed and the contributions address the fields of listening, reading, writing, speaking and communication strategies, looking at common characteristics of the "expert teacher" and the "expert learner."